BAHAN AJAR MULTI-INTELEGENSIA BERBASIS ANIMASI SEBAGAI MEDIA UNTUK MENINGKATKAN PRESTASI DAN MOTIVASI BELAJAR MAHASISWA TADRIS KIMIA IAIN WALISONGO SEMARANG - Udaibah, Wirda (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2013)
A study concerning the application of multi-intelligence teaching materials based animationÂ to improve student achievement and student motivation in Chemistry Tadris IAIN WalisongoÂ Semarang on the material structure of the metal packing have been observed. Research usingÂ cluster random sampling technique. The samples were divided into experimental class (a classÂ that uses animation-based learning media) and control classes (classes that do not useÂ animation-based learning media). Data analysis showed that there were significant differencesÂ between the experimental class and the control class. On the one hand the test calculationsÂ obtained tÂ countÂ less than tÂ tableÂ with dk = 20 with ï¡ = 5%, then we can conclude that Ha is accepted,Â which means that the average student learning outcomes using media-based learning animationÂ (the experimental group) was better than average of chemistry student learning outcomes that doÂ not use the animation (the control group). As well as in the assessment of the affective aspects.Â Students who get the lesson with animated media proved to have the learning motivation betterÂ than students who do not use animation media. Therefore it can be concluded that the animationbased learning media is effective to improve student achievement and student learning motivation.Keywords: Multi-intelligence Animation-basedÂ